Development of canned sisig - Collado, Sarah Jean G.; Francisco, Ma. Leonora dL. (1998.)
ABSTRACT The study was undertaken to develop canned sisig. Sensory evaluation on three sisig recipes was done to determine the most acceptable formulation for canning. Sisig recipe from Monterey Meat Shop was chosen based on the highest mean score for general acceptability. The product was found to be moderately liked by the panelists. Heat penetration study of sisig in 1F cans processed at a retort temperature of 250 F for one hour was done on three production runs. The cold point was at the geometric center of the can since it is a conduction heating product. The pH was found to be 4.0 due to acidification. Process schedule for canned sisig was calculated based on the heating parameters obtained and the thermal resistance of the reference organism. Clostridium sporogenes (PA 3679), D-value of 1.5 minutes and z-value of 18. PA 3679 was used as the reference organism because the product is composed of meat pieces and there is a chance that they can still thrive regardless of the low pH. Lethality of the process was computed using the graphical method. The process gave a lethality value higher than the required 7.5 minutes. Thus, the one hour process was more than adequate to render the product commercially sterile. Cut-out tests, microbiological examination and sensory evaluation were conducted to verify the processed product. Results of cut-out tests showed no signs of spoilage. Microbiological results were within the acceptable range and were considered as safe. Sensory evaluation showed no significant difference between samples from the three production runs.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food, Canned